Isolation and characterization of Schwanniomyces alluvius amylolytic enzymes. - Wilson, J J (1982)
The extracellular amylolytic enzymes of Schwanniomyces alluvius were studied to determine future optimization of this yeast for the production of industrial ethanol from starch. Both alpha-amylase and glucoamylase were isolated and purified. alpha-Amylase had an optimum pH of 6.3 and was stable from pH 4.5 to 7.5. The optimum temperature for the enzyme was 40 degrees C, but it was quickly inactivated at temperatures above 40 degrees C. The Km for soluble starch was 0.364 mg/ml. The molecular weight was calculated to be 61,900 +/- 700. alpha-Amylase was capable of releasing glucose from starch, but not from pullulan. Glucoamylase had an optimum pH of 5.0 and was stable from pH 4.0 to greater than 8.0. The optimum temperature for the enzyme was 50 degrees C, and although less heat sensitive than alpha-amylase, it was quickly inactivated at 60 degrees C. Km values were 12.67 mg/ml for soluble starch and 0.72 mM for maltose. The molecular weight was calculated to be 155,000 +/- 3,000. Glucoamylase released only glucose from both soluble starch and pullulan. S. alluvius is one of the very few yeasts to possess both alpha-amylase and glucoamylase as well as some fermentative capacity to produce ethanol.